Presence of citrus greening disease in Bangladesh and a new method for rapid diagnosis - Hondrade, Rosa Fe; Hondrade, Edwin; Zheng, Lianqing; Elazegui, Francisco; Duque, JLE; Mundt, Christopher C; Vera Cruz, Casiana M; Garrett, Karen A (PeerJ, 2016)
Including food production in non-food systems, such as rubber plantations and biofuel or bioenergy crops, may contribute to household food security. We evaluated the potential for use of rice, mungbean, rice cultivar mixtures, and rice intercropped with mungbean in experiments planted in young rubber plantations in the Arakan Valley of Mindanao. Rice mixtures consisted of two- or three-row strips of cultivar Dinorado, a cultivar with higher value but lower yield, and high-yielding cultivar UPL Ri-5. Rice and mungbean intercropping treatments consisted of different combinations of two- or three-row strips of rice and mungbean. We used generalized linear mixed models to evaluate the yield of each crop alone and in the mixture or intercropping treatments, as well as a land equivalent ratio for yield, and weed biomass, the severity of panicle blast, brown spot, and brown leaf spot, and rice bug abundance. We also analyzed the yield ranking of each cropping system across site-year combinations to determine mean relative performance and yield stability. When weighted by their relative economic value, UPL Ri-5 had the highest mean performance, but with decreasing performance in low-yielding environments. A rice and mungbean intercropping system had the second highest performance, tied with high-value Dinorado but without decreasing performance in low-yielding environments. Rice and mungbean intercropped with rubber have been adapted by farmers in the Arakan Valley.